Validation of Mercury Speciation Analysis in River Around Artisanal Small-Scale Gold Mining Area in West Nusa Tenggara, Indonesia - Dhony Hermanto; Nurul Ismillayli; Nindi Herdiyanti; Siti Raudhatul Kamali; Soraya Aulia (Research Center of Inorganic Materials and Coordination Complexes, FMIPA Universitas Sriwijaya, 2022)
A method for determining mercury concentration using a mercury analyzer in a river water sample was validated according to ISO/IEC 17025. Analytical performance including linear range, limit of detection, precision and accuracy were evaluated. Mercury speciation profile was obtained from Pelangan River at three areas within Dusun Rambut Petung, an area with the highest amount of artisanal small-scale gold mining (ASGM) in Lombok, West Nusa Tenggara. Then, their concentration in each species was measured using sequential extraction. Good curve linearity was obtained in the concentration range of 0.1-5.0 µg/L and the limit of detection was 0.014 µg/L. The developed method has good precision and accuracy with a RSD value <10% and a recovery of 94.16-101.91%. The detected fraction of mercury in the Pelangan river is organomercury, elemental mercury, and sulfide-bound species with each concentration of 0.732±0.032; 0.350±0.027; and 0.850±0.027 µg/L, respectively. The measurement results showed conformity with the reference method using CV-AAS. Therefore, this method can be applied to determine mercury levels in water for monitoring environmental quality.